Analisis Isi Kualitatif Konten Influencer di Instagram dalam Kampanye Tokopedia By Me - Salsabila Fadhilah Ramadhan; Nani Kurniasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
With the constant development of technology, companies must adapt to new promotion methods. Social Media marketing is a key strategy for promotion in the new era, one of which is through Instagram, where communication strategies are no longer only done only through text, but also through visual posts like photos or videos. One of the most sought after promotion methods is through influencers. This study was made to analyze the hidden contexts behind influencer’s promotional posts, specifically in the Tokopedia ByMe campaign. The researcher used descriptive qualitative content analysis method to analysize photos from 5 main categories of influencers, which are fashion, beauty, technology, traveling and parenting. Through the data obtained, the researcher determined that the majority of products promoted by influencers are in accordance with the main theme of their accounts, that there is consistency in the influencers photos that help the implementation of promotional strategies, and among the five categories, the parenting category is the content that has the most engagement.